SIMPLE PRESS TOOL DESIGN AS A SUPPORTING TOOL FOR FORMING PLATES WITH A THICKNESS OF 3 MM - sulaeman, aldi; Santosa, Aa (Universitas Majalengka, 2023)
The press tool is one of the combined Jig and Fixture tools that can be used to form and cut metal by means of emphasis. The working process of this tool is based on the compressive force passed on by Punch to cut or shape the workpiece according to the desired geometric and size. This research aims to design a cutting machine for sheet metal forming processes that are able to improve the production process in industry. In this study, the author designed the components of a progressive type presstool machine in the process of making clamps with a thickness of 3mm with software inventor design media. Includes components shanks (St.60), top plate (St.60), bearing locator (St.40), bottom plate (St.60), punch (SKD-11), dies (SKD-11), pillar shaft (St.40), spring (St.40). Analysis of calculations carried out in this study produces a cross-sectional area of the shear field (132mm2), shear voltage (32 kg/mm2), Formation style (4,224kg), presstool engine power (1267.2 watts/168.9688 HP). Press tools are designed to make clamps made of steel plates with a thickness of 3 mm. From the design results obtained the dimensions of the tool as follows the length of 450 x 400 x 542 mm. The results of press tool type of precision equipment used to form or cut workpiece materials according to needs and to increase production in industry